A multi‐input‐single‐output high step‐up DC‐DC converter with low‐voltage stress across semiconductors. (22nd July 2019) - Mohseni, Parham; Hosseini, Seyed Hossein; Sabahi, Mehran; Maalandish, Mohammad
Summary: In this paper, a new extendable high step‐up multi‐input‐single‐output dc‐dc converter is presented. The proposed converter is composed based on the conventional boost converter and conventional buck‐boost converter. The benefits of the proposed converter consist of the simple control of each duty cycle and low‐voltage stress across the semiconductors. Therefore, conduction losses can be reduced by using the switch with lower resistance r DS(on) . The presented converter is flexible to obtain the high power level with the proper selection of duty cycle values. Therefore, the presented converter is controllable in different power levels of input sides. In fact, the proposed converter supports the operation of multiple input sources without any changes in the structure of the topology. The dynamic modeling and efficient multivariable controller design with dynamic responses for the proposed converter are analyzed completely. To confirm the performance of the presented converter, mathematical analysis and simulation results are presented. In addition, the comparison between the presented converter and some other topologies is provided. In order to illustrate the efficient operation of the presented converter, a laboratory prototype for a 425 V/300 W with 40‐ and 45‐V input voltages and 95.62% efficiency is implemented.